Numerical analysis and validation of an optical parametric oscillator considering crystal thermal effects - Wang, Rui; Wang, Shuilan; Tan, Jiacheng; Li, Yeqiu; Dai, Qin (Frontiers in Physics, 2023)
In this paper, a calculation model of the optical parametric oscillation process considering the crystal thermal effects is proposed. Based on existing model, we combine the set of three-wave coupled equations with the Sellmeier equation. In order to optimize the calculation of the nonlinear process, a temperature variable t is introduced to describe the heat generated by the laser crystal during operation. The waveforms under different pump power are analyzed. The effects of the reflectivity of the output mirror on the OPO threshold and inverse conversion are investigated. In addition, the optimal reflectivity under different pump power can be estimated. Based on simulation results, experiments are also performed in the near-infrared 1.57µm band and mid-infrared 3.15µm band. The experimental results are compared with the results of this model and the model without considering crystal thermal effects. The experimental results are consistent with the improved theoretical results. It verifies that the proposed theoretical model can simulate the energy conversion process of OPO, and provide a theoretical basis for optimizing the parameters of the OPO output mirror and improving the efficiency of the parametric wave conversion.